Maternal adverse effects with different loading infusion rates of antenatal magnesium sulphate for preterm fetal neuroprotection: the IRIS randomised trial. (6th January 2014) - Bain, ES; Middleton, PF; Yelland, LN; Ashwood, PJ; Crowther, CA
<x xml:space="preserve">Abstract</x> Objective To evaluate a slower (compared with a standard) infusion rate of the loading dose of magnesium sulphate for preterm fetal neuroprotection as a strategy to reduce maternal adverse effects. Design Randomised controlled trial. Setting South Australian maternity hospital. Population Fifty‐one women at <30 weeks of gestation, where birth was planned or expected within 24 hours. Methods Women received a loading infusion of 4 g of magnesium sulphate over either 60 or 20 minutes (followed by maintenance of 1 g/hour until birth, or for up to 24 hours). Main outcome measures Any maternal adverse effects associated with the infusion. Results Overall, 71% of women experienced adverse effects during the first hour of their infusion; the difference between groups was not significant [15/25 (60%) 60‐minute loading; 21/26 (81%) 20‐minute loading; risk ratio (RR) 0.74; 95% confidence interval (95% CI) 0.51–1.08]. Although no serious maternal complications occurred, adverse effects led to three women ceasing the loading treatment (1/25 in the 60‐minute loading group; 2/26 in the 20‐minute loading group; RR 0.52; 95% CI 0.05–5.38). Women in the 60‐minute loading group experienced significantly less warmth and flushing at 20 minutes into the infusion (7/25 in the 60‐minute loading group; 15/26 in the 20‐minute loading group; RR 0.49; 95% CI 0.24–0.99). No other differences between groups for maternally reported and clinical adverse effects were shown. Conclusions A slower rate of administering the loading dose of magnesium sulphate did not reduce the occurrence of maternal adverse effects overall. Flushing and warmth at 20 minutes into the infusion was reduced with a slower infusion.